BCR-ABL1 transcript decline ratio combined BCR-ABL1(IS) as a precise predictor for imatinib response and outcome in the patients with chronic myeloid leukemia - Cai, Zhimei (J Cancer, 2020)
Purpose: The early BCR-ABL1 reduction had the prognostic impact of the chronic-phase chronic myeloid leukemia (CML-CP) patients. This study was to find a more precise early prognosis index at 3 months in the patients with newly diagnosed CML-CP, especially for the patients with BCR-ABL1(IS) >10%. Methods: We retrospectively analyzed the data of 79 newly diagnosed CML-CP patients from October 2013 to April 2017. All patients took imatinib regularly and continuously and monitored BCR-ABL1 transcript level at baseline and 3, 6, 9, 12, 18 months after starting imatinib treatment. Results: Among the 44(55.7%) patients with BCR/ABL1(IS) ≤10% at 3 months after imatinib treatment, 12(27.3%) cases did not achieve major molecular response (MMR) at 12 months, and 7(14.9%) patients with the halving time BCR-ABL1 transcript ≤40 days failed to achieve MMR at 12 months. However, approximately twenty-six percent of the patients with BCR-ABL1(IS) >10% still obtained MMR. Moreover, the patients with BCR-ABL1(IS) ≤10% and halving time ≤40 days had a significantly better MMR than that of the patients with the BCR-ABL1(IS) ≤10% and halving time >40 days (88.6% versus 11.1%, P <0.001). However, the patients with the BCR-ABL1(IS) >10% and halving time >40 days rarely achieved MMR at 12 months. Conclusion: These data indicated that the halving time of BCR-ABL1 transcript was also an important prognostic factor as that of the BCR-ABL1(IS). Combined observations of these two prognosis indexes are more accurate predictor for the long-term molecular response, especially for the CML-CP patients with BCR-ABL1(IS) >10%, and which is helpful for TKI switching as early as possible to improve patients' survival and reduce drug costs.